The Regulation of Growth in Developing, Homeostatic, and Regenerating Tetrapod Limbs: A Minireview - Wells, Kaylee M.; Baumel, Mary; McCusker, Catherine D. (Frontiers in Cell and Developmental Biology, 2022)
The size and shape of the tetrapod limb play central roles in their functionality and the overall physiology of the organism. In this minireview we will discuss observations on mutant animal models and humans, which show that the growth and final size of the limb is most impacted by factors that regulate either limb bud patterning or the elongation of the long bones. We will also apply the lessons that have been learned from embryos to how growth could be regulated in regenerating limb structures and outline the challenges that are unique to regenerating animals.